For more sun - Joint Entertainment International ([Taipei, Taiwan : Joint Entertainment International, 2006)
At Taiwan's top university, a dedicated professor guides his students on a valueble journey from theory to practice to build a solar powered car for the 2005 World Solar Challenge in Australia. After months of unflagging efforts, their finished products FORMOSUN III is ready to portake in the 3,000 kilometer race. Effective planning, strong teamwork, and a large dose of determination are now required to get the team through the final part of the challenge and turn their dreams of success into reality
DVD format
Subtitles in Spanish
Keywords: Solar energy -- Taiwan